English Language Learning in Language Academic Preparation Program (LAPP): an Autoethnography - Risma Fahrul Amin; Suhono Suhono; Erikson Saragih; Marzia Khatan Smita (CV. Creative Tugu Pena, 2025)
This autoethnographic study examines the lived experiences of learning English for Academic Purposes (EAP) within the Language Academic Preparation Program (LAPP), a key component of the Program Persiapan Studi Lanjut (PPSL) at UIN Sultan Syarif Kasim Riau. Drawing upon personal reflections and research journals, the study investigates how culturally responsive pedagogy, local wisdom, and immersive experiences shape academic language development. By engaging in activities such as traditional ceremonies, local arts performances, culinary practices, and educational field visits, the program contextualized English learning in ways that enhanced learner engagement and reinforced cultural identity. The findings suggest that EAP instruction becomes more effective and transformative when it integrates local cultural content with authentic learning contexts. Furthermore, the study demonstrates that autoethnography provides a valuable lens for capturing the emotional, intellectual, and pedagogical dimensions of language education. The main contribution of this research lies in proposing an alternative model of EAP instruction that is not only academically rigorous but also culturally grounded, offering new insights for the development of contextually relevant language education programs in Indonesia and beyond.